Accumulation of xylem transported protein at pit membranes and associated reductions in hydraulic conductance - Neumann, Peter M. (Oxford University Press, 2010)
Proteins and traces of polysaccharide are the only polymeric colloids consistently transported in the xylem sap of plants. The hypothesis that such proteins could have physical inhibitory effects on xylem water transport was investigated. Ovalbumin, with a molecular weight of 45 kDa and a molecular diameter of 5.4 nm, is an inert, water-soluble protein that is midway along the size range of endogenous xylem sap proteins. Solutions of ovalbumin conjugated to a fluorescent marker and supplied to transpiring shoot explants of tobacco (Nicotiana tabacum L.) and olive (Olea europaea L.) were shown by confocal laser scanning microscopy to accumulate specifically at wall-based pit membranes that connect neighbouring xylem conduits. In addition, pressure-induced perfusion of micro-filtered ovalbumin solutions, at concentrations similar to those of endogenous xylem sap proteins, through the xylem of tobacco stem or olive twig segments resulted in the retention of c. 40% of the ovalbumin and reductions in the axial hydraulic conductance of the xylem. Smaller molecules such as Texas Red 3000 (MW 3 kDa) and Alexafluor 488–cadaverin conjugates (MW 0.64 kDa) did not show similar characteristics. The partial reduction in xylem hydraulic conductance appeared to be related to the accumulation of ovalbumin at xylem pit membranes and the consequent fouling of trans-membrane water-conducting pores with smaller diameters than those of the ovalbumin molecules. Potential implications of these novel findings for whole-plant water relations are considered.